Teachers’ Perception of Inquiry-based Science Education in Indian Primary School - Bansal, Garima (INDIAN EDUCATIONAL REVIEW, 2017)
Within science education reforms, a pedagogical shift from a teacher-centred, textbook-based instructional paradigm to a student-centred, inquiry-based model is called for. Despite strong theoretical grounding, there is limited evidence that primary teachers effectively engage students in pedagogical approaches associated with inquiry-based science curriculum in classroom settings. This study examines the constraints faced by primary school teachers in practicing inquiry-based environmental studies curricula using multiple case study design. Classroom observations, semi-structured interviews, and focussed group discussions were used for conducting cross-sectional thematic analysis of the data. It emerged that owing to accountability pressures, non-synchronisation between curriculum and assessment practices backed by their personal beliefs in lecture method receded inquiry based teaching-learning practices in classrooms. Finally, possibilities for embedding inquiry-based science in classroom practices are explored.